Efficacy of core needle biopsy in the diagnosis of pediatric extracranial solid malignancies: A 10-year study - Arun Kumar Loganathan; Tarun John Jacob; Leni Grace Matthew; Vinu Moses; Shyam Kumar Nidugala Keshava; Anne Jennifer Priscilla; Jujju Jacob Kurian (Wolters Kluwer Medknow Publications, 2022)
Introduction: Core needle biopsies of solid masses in children are a minimally invasive technique. It guides to a definitive diagnosis and facilitates management. Aims and Objectives: To determine the accuracy, sensitivity, and specificity of core needle biopsies in diagnosing pediatric solid masses. Materials and Methods: A retrospective analysis of 430 children, who underwent core needle biopsy for solid masses between January 2007 and December 2016 at CMC Vellore, was done. Results: Retroperitoneal and intra-abdominal masses constituted 66% of cases. Real-time image guidance was used in 44% of cases. An accurate diagnosis was obtained in 93.6% of cases, while results did not correlate with the final diagnosis in 3.4%. Three percent had inadequate or necrotic tissue. None of the children had postprocedure complications. Conclusion: Core needle biopsies serve as good diagnostic modality, with minimal risks, in making a conclusive diagnosis and deciding on the line of management.